2018
DOI: 10.1111/pan.13324
|View full text |Cite
|
Sign up to set email alerts
|

The prediction probabilities for emergence from sevoflurane anesthesia in children: A comparison of the perfusion index and the bispectral index

Abstract: Both the perfusion index and bispectral index performed comparably well in predicting awakening and different arousal levels when emerging from sevoflurane anesthesia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…However, PLE values rose faster than BIS values from ROC to full recovery of orientation, and at full recovery of orientation, the PLE value reached the preanesthetic value, whereas the BIS value remained approximately 12 lower than baseline. These results are consistent with those of an earlier study, which reported that the BIS value reached approximately 85% of the preoperative baseline value at awakening 30. Failure of BIS to return to the preanesthetic value at full recovery of orientation suggests a potential difference between PLE and BIS with respect to their sensitivity to residual concentrations of anesthetics.…”
Section: Discussionsupporting
confidence: 91%
“…However, PLE values rose faster than BIS values from ROC to full recovery of orientation, and at full recovery of orientation, the PLE value reached the preanesthetic value, whereas the BIS value remained approximately 12 lower than baseline. These results are consistent with those of an earlier study, which reported that the BIS value reached approximately 85% of the preoperative baseline value at awakening 30. Failure of BIS to return to the preanesthetic value at full recovery of orientation suggests a potential difference between PLE and BIS with respect to their sensitivity to residual concentrations of anesthetics.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have compared the performance of different EEG-derived monitors and other monitors in the patients. [6,14,22,23] Most of these studies reported comparable prediction probabilities for the different monitor types. In the present study, BIS and PSI yielded similar prediction probabilities for distinguishing the maintenance state from recovery state in children.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the performance of different EEG-derived monitors and other monitors in the patients. [6,14,21,22] Most of these studies reported comparable prediction probabilities for the different monitor types. In the present study, BIS and PSI yielded similar prediction probabilities for distinguishing the steady state from recovery state in children.…”
Section: Discussionmentioning
confidence: 99%